Membangun Model Terpadu Untuk Sistem Informasi Berbasis Komputer - Michael Iskandar (Bina Ekonomi, 2001)
Models are widely used in theoretical discourses on real-world subjects, often forming the basis on which entire chapters and even books are written. This is also true in the study of management information systems in general and computer-based information systems (CBISs) in particular. Considering that there is a particularly intensive use of modeling in this field, it is perhaps surprising that authors create and employ vastly different models to explain the CBIS. This paper is an effort to create a new, integrated model of the CBIS. First, all (or as many as possible) of the systems, concepts, and technologies that are usually associated with CBISs are reclassified using its most distinctive characteristic(s). This leads to the discovery that there are no less than six criteria used to identify them and, what is more, they are often not mutually exclusive. These criteria are: (1) management level support, (2) type of information processing performed, (3) functional unit supported, (4) computer technology used, (5) the presence of functional integration, if any, and (6) whether or not the system extends beyond the organization. Finally, a new model is created based on these findings, and all the systems, concepts and technologies analyzed are allocated their proper place within it.